1996
DOI: 10.1046/j.1365-2818.1996.67430.x
|View full text |Cite
|
Sign up to set email alerts
|

Early mineralization of matrix vesicles in the epiphyseal growth plate

Abstract: Matrix vesicles (MVs) induce the primary mineralization in collagen-rich hard tissues such as bone, mineralizing cartilage and dentine. Calcium and phosphate ions accumulate at the inner MV membrane. This accumulation takes place in association with phospholipids alone and/or in association with Annexin V, which displays Ca ion channel activity when inserted in membranes; consequently, Annexin V may be involved in Ca uptake by matrix vesicles. The first crystal nuclei are formed at these macromolecules of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 36 publications
(65 reference statements)
2
20
0
Order By: Relevance
“…High-resolution ultrastructural studies have shown that center-to-center distances between particles in the inner face of matrix vesicle membranes are consistent with calcium phosphate nucleation (Plate et al, 1996). Isolated matrix vesicles also promote mineralization in vitro (Boskey et al, 1997).…”
Section: Do Crystal Chambers Nucleate Crystals?mentioning
confidence: 93%
“…High-resolution ultrastructural studies have shown that center-to-center distances between particles in the inner face of matrix vesicle membranes are consistent with calcium phosphate nucleation (Plate et al, 1996). Isolated matrix vesicles also promote mineralization in vitro (Boskey et al, 1997).…”
Section: Do Crystal Chambers Nucleate Crystals?mentioning
confidence: 93%
“…Likewise, a similar layered structure has also been observed in clay minerals in an exclusively inorganic system without cells or proteins (Vali and Bachmann, 1988;Vali et al, 2001). A multi-step mineralization pattern for hydroxyapatite formation has also been reported during the initial mineralization events in matrix vesicles found in cartilage extracellular matrix (Kirsch et al, 1997;Plate et al, 1996).…”
Section: Nucleation and Growth Of Hydroxyapatite In Biological Systemsmentioning
confidence: 55%
“…Other challenges are to understand the atomic-level chemistry that occurs within the calcifying vesicles that results in the deposition of the very first crystals, and whether this process is inorganically driven or derives at least initially from the loss of potent mineralization inhibitors such as pyrophosphate and fetuin-A. While the mode of mineralization in matrix vesicles and their role in both physiologic and ectopic calcification have been studied extensively (Anderson, 1969(Anderson, , 1990Anderson et al, 2004;Bonucci, 1970;Hsu and Anderson, 1978;Kirsch et al, 1997;Plate et al, 1996), there is little data available on the intracellular process we describe here. While needing further study, we propose that calcification specifically associated with intracellular, membrane-bounded organelles triggered by dysregulated cell processes represents an additional mechanism for inducing ectopic calcification.…”
Section: Intracellular Vesicle Calcification In Mdck Epithelial Cellsmentioning
confidence: 99%
“…In hard tissues, such as bone and mantle dentin, it is generally accepted that the mineralization process starts within extracellular-bond structures known as matrix vesicles (MV) (Anderson, 1967;Bonucci, 1967;Boskey, 1999b;Kirsch, et al, 1997b;Plate, et al, 1996;Wiesmann, et al, 2005). These MV are the result of a polarized budding process that occurs in osteoblasts, odontoblasts and in chondrocytes present in the epiphyseal growth plate, a region where longitudinal bone growth occurs.…”
Section: Mineralization Of Bonementioning
confidence: 99%
“…The uptake of calcium ions is parallel to the inward movement of phosphorous ions, which occurs via the activation of sodium-dependent phosphate transporters. According to some studies, the phosphatidylserine first binds to calcium ions to form a calcium-phospholipid-phosphate complex (Anderson, 1967;Bonucci, 1967;Plate, et al, 1996). This binding with calcium ions, and phosphate ions, induces the formation of nucleation regions (Morris, et al, 1992;Plate, et al, 1996).…”
Section: Mineralization Of Bonementioning
confidence: 99%